An empirical review on the risk factors, therapeutic strategies and materials at nanoscale for the treatment of oral malignancies. (July 2022) - Azees, Parveez Ahamed Abdul; Natarajan, Suganthy; Amaechi, Bennett T.; Thajuddin, Nooruddin; Raghavendra, Vinay B.; Brindhadevi, Kathirvel; Pugazhendhi, Arivalagan; Phuong, Tran Nhat
Abstract: Oral health of an individual is a key factor in initiation of oral cancer. Oral cancer can be classified into five stages and involves several risk factors. Novel and safe therapeutic procedures are necessary for this type of aggressive cancer with high mortality and poor diagnosis. Surgery and radiation are common procedures for treatment of oral cancer. Nanomedicine is a recent avenue in oncology treatment and management and therefore, recent research on using nanomaterials for treatment of oral cancer is on the rise. This review intends to report the available literatures that explore the potential risk factors that could lead to the incidence of oral cancer and nanotherapeutics to treat it. Graphical Abstract: ga1 Highlights: Consumption of Tobacco and Alcohol Consumption examined. Current Therapeutic Strategies against oral cancers were discussed. Toxicity associated with conventional chemotherapy explained. Nanotechnology-based Strategies in Oral Cancer treatment were investigated.